2021
DOI: 10.1002/ece3.7147
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intrasex habitat partitioning in the highly dimorphic southern elephant seal

Abstract: Partitioning resources is a key mechanism for avoiding intraspecific competition and maximizing individual energy gain. However, in sexually dimorphic species it is difficult to discern if partitioning is due to competition or the different resource needs of morphologically distinct individuals. In the highly dimorphic southern elephant seal, there are intersexual differences in habitat use; at Iles Kerguelen, males predominantly use shelf waters, while females use deeper oceanic waters. There are equally mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 78 publications
(101 reference statements)
2
34
0
Order By: Relevance
“…These foraging behaviours are largely consistent with previous work [27][28][29]31,40]. Southern elephant seals (Mirounga leonina), the sister taxa to northern elephant seals, also show similar sexual segregation in foraging behaviours [42][43][44][45].…”
Section: Discussionsupporting
confidence: 90%
“…These foraging behaviours are largely consistent with previous work [27][28][29]31,40]. Southern elephant seals (Mirounga leonina), the sister taxa to northern elephant seals, also show similar sexual segregation in foraging behaviours [42][43][44][45].…”
Section: Discussionsupporting
confidence: 90%
“…First, we calculated the area (km 2 ) of each UDi by counting the number of 5 × 5 km cells visited by each seal and compared these among the three deployment locations using a GLMM which included deployment duration as a random term to account for animals with longer durations potentially having larger UD areas. Seal standard length (m) was included in the model to account for animal size potentially being an important source of individual variation in space use (Hindell et al, 2021). We used length as it was the only morphometric measure common to all studies.…”
Section: Individual Utilisation Distributions Statisticsmentioning
confidence: 99%
“…Photopoulou et al (2020) reported that male Weddell seals spent more time in highsalinity shelf water masses at depth, benthically diving, while females ventured off the continental shelf and visited warmer, shallower water masses while undertaking a mix of benthic and pelagic dives. Our sample did not include sub-adults or juveniles, age classes which have very different distributions in other Southern Ocean pinnipeds (e.g., elephant seals, Hindell et al, 2021). Burns et al (1999) reported that some weaned Weddell seal pups from McMurdo Sound in the southern Ross Sea dispersed widely, others did not, but all stayed relatively close to the Antarctic coastline.…”
Section: Regional Variation In Habitat Use Is Explained By Site Variability Not Inherent Population Level Behavioural Differencesmentioning
confidence: 99%
“…Animalborne sensors also provide data on animal behavior in relation to in situ environmental conditions undertaking adaptive sampling by seeking areas of both physical and biological interest (Guinet et al, 2014;Labrousse et al, 2017aLabrousse et al, ,b, 2018Nachtsheim et al, 2019). Linking physical and biological data in this way allows us to quantify the differences in environmentally mediated behavior at the population, species and community levels (Chambault et al, 2016;Hindell et al, 2016Hindell et al, , 2017Hindell et al, , 2021McMahon et al, 2017;Bestley et al, 2020;Citta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%